ANALYSIS AND DEFINITION OF THE ESSENCE OF THE CONCEPT OF “SOCIOCULTURAL VALUES” - Zaredinova Elvira Rifativna (International Journal of Innovative Technologies in Social Science, 2020)
The results of the theoretical analysis of the essential-functional nature of sociocultural values at the present stage of scientific research are considered in the article. It is determined that the concept of “value” is leading to the axiological approach. Different approaches to understanding the content of sociocultural values as a scientific category are characterized. The essence of the concept of “sociocultural values” is defined, the characteristic features are presented. The necessity of sociocultural values formation at modern student youth in the conditions of educational process of institution of higher education is revealed. It is emphasized that the educational environment of institution of higher education promotes formation of value and semantic sphere of students.